MATERIALISM, AFFLUENZA AND FRUSTRATION AMONG DRUG ABUSERS IN PAKISTAN (Contemporary Journal of Social Science Review, 2025)
The present study aimed to examine the relationship between materialism, affluenza, and frustration among drug abusers in Pakistan. The study adopted a cross-sectional correlational research design and employed a purposive sampling technique to collect data from drug abusers admitted to public and private rehabilitation centres in Pakistan. Data were collected using three standardized questionnaires, namely the Material Values Scale, the Affluenza Scale, and the Frustration Discomfort Scale. Correlational analysis revealed significant relationships among the study variables, including materialism, affluenza, and frustration. Independent samples t-test results indicated no significant gender differences with respect to the study variables. The findings are discussed in the light of previous literature, and recommendations as well as implications for future research and practice are provided.